MEASURING AND ANALYZING THE ROLE OF FOREIGN DIRECT INVESTMENT POLICIES IN DIVERSIFYING EMPLOYMENT IN THE OMANI ECONOMY FOR THE PERIOD 2002-2022 - Salam Kazem Shani (Scholar Express Journals, 2025)
This study looks at how employment in the Omani economy was diversified by foreign direct investment (FDI) between 2002 and 2022. Numerous economies, both established and developing, have implemented certain economic strategies meant to expand work prospects and diversify employment sources. Attracting foreign direct investment (FDI) is one such policy that helps target particular economic activities that are essential to job development and employment diversification. By using ARDL model, the study uses sophisticated econometric analysis to quantify the effect of FDI (across several economic sectors) on employment. Several important insights are revealed by the research. Short-term employment benefits from foreign direct investment (FDI) in the trade, hotel, and restaurant industries are statistically significant. FDI benefits the trade sector over the long run, but it may not have a statistically significant effect on employment in other economic sectors.
Keywords: Foreign Direct Investment; Economic Diversification; Employment